PENGARUH LATIHAN ROCKET JUMP TERHADAP EXPLOSIVE POWER OTOT TUNGKAI PADA TIM BOLA VOLI PUTRA SMA NEGERI 2 RAMBAH HILIR KABUPATEN ROKAN HULU - Setiawan, Bayu; Slamet, Slamet; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research is the lack of explosive power of leg muscle during smash and block on male volleyball team of SMA Negeri 2 Rambah Hilir Rokan Hulu Regency. Based on these problems the writer gives the form of rocket jump exercises. This study was conducted to know how much the influence of rocket jump exercises on the explosive power of leg muscles on the male volleyball team SMA Negeri 2 Rambah Hilir, so that when doing the jump smash and block the player will get maximum jump results. This type of research is a experimental research with design one group pretest-posttest design research. The population in this study is male volleyball team of SMA Negeri 2 Rambah Hilir which amounted to 10 people. While the sampling technique used is total sampling, where the entire population of 10 people used as sample. With vertical jump test instrument then descriptive analysis and normality test using liliefors test at significant level α (0.05) the average result of pretest vertical jump is 50,6. Furthermore, by giving the rocket jump exercise for 16 times on the volleyball team which amounted to 10 people, Then the posttest vertical jump generates to average of 59,6. Based on the results of pretest and posttest data analysis there is a difference in numbers that increased by 9,0. From t test analysis yield Thitung equal to 7,63 and Ttabel equal to 1,833 mean thitung > ttabel. It can be concluded that rocket jump exercises affect the results of explosive power of leg muscle on the male volleyball team SMA Negeri 2 Rambah Hilir.Keywords: Rocket Jump, The Explosive Power Of Leg Muscle